Innate stimulation of B cells ex vivo enhances antibody secretion and identifies tumour-reactive antibodies from cancer patients. (5th December 2021) - Karagiannis, Panagiotis; Correa, Isabel; Chauhan, Jitesh; Cheung, Anthony; Dominguez-Rodriguez, Diana; Terranova-Barberio, Manuela; Harris, Robert J; Crescioli, Silvia; Spicer, James; Bokemeyer, Carsten; Lacy, Katie E; Karagiannis, Sophia N
Abstract: Human B cells and their expressed antibodies are crucial in conferring immune protection. Identifying pathogen-specific antibodies following infection is possible due to enhanced humoral immunity against well-described molecules on the pathogen surface. However, screening for cancer-reactive antibodies remains challenging since target antigens are often not identified a priori and the frequency of circulating B cells recognizing cancer cells is likely very low. We investigated whether combined e x vivo culture of human B cells with three innate stimuli, interleukin-17 (IL-17), B-cell activation factor (BAFF), and the toll-like receptor 9 (TLR-9) agonist DNA motif CpG ODN 2006 (CpG), each known to activate B cells through different signalling pathways, promote cell activation, proliferation, and antibody production. Combined IL-17+BAFF+CpG prolonged B-cell survival and increased proliferation compared with single stimuli. IL-17+BAFF+CpG triggered higher IgG secretion, likely by activating differentiated, memory and class-switched CD19 + CD20 + CD27 + IgD - B cells. Regardless of anti-FOLR antibody seropositive status, IL-17+BAFF+CpG combined with a monovalent tumour-associated antigen (folate receptor alpha [FOLR]) led to secreted antibodies recognizing the antigen and the antigen-expressing IGROV1 cancer cells. In a seropositive individual, FOLR stimulation favoured class-switched memory B-cell precursors (CD27 - CD38 - IgD - ), class-switched memory B cells and anti-FOLR antibody production, while IL-17+BAFF+CpG combined with FOLR, promoted class-switched memory B-cell precursors and antibody-secreting (CD138+IgD-) plasma cells. Furthermore, IL-17+BAFF+CpG stimulation of peripheral blood B cells from patients with melanoma revealed tumour cell-reactive antibodies in culture supernatants. These findings suggest that innate signals stimulate B-cell survival and antibody production and may help identify low-frequency antigen-reactive humoral responses.